1966
DOI: 10.1002/pol.1966.150040624
|View full text |Cite
|
Sign up to set email alerts
|

A new series of organoboranes. VII. The preparation of poly‐m‐carboranylenesiloxanes

Abstract: SynopsisThis paper describes the preparation of the first members of a new series of polysiloxanes characterized by having m-carborane nuclei in the backbone of the polymers. Although neither hydrolysis of 1,7-bis( chlorodialkylsilyl)-mcarborane monomers nor catalytic dehydration of the corresponding dihydroxy compounds would proceed to give the type of polysiloxanes desired, the polymers were readily prepared by the ferric chloridecatalyzed elimination of an alkyl halide from equimolar mixtures of dichloro-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…16 Polymers above I ,000-2,000 in molecular weight could not be prepared by the conventional route of hydrolysis of 1, 7 -bis( chloro-dimethylsilyl)m-carborane, this failure being ascribed to the extremely electronegative nature of the carborane nucleus. Success was achieved by ferric chloride-catalyzed elimination of an alkyl halide from equimolar mixtures of dichloroand dialkoxysilanes at temperatures of 140-165°C.…”
Section: Decaborane Skeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Polymers above I ,000-2,000 in molecular weight could not be prepared by the conventional route of hydrolysis of 1, 7 -bis( chloro-dimethylsilyl)m-carborane, this failure being ascribed to the extremely electronegative nature of the carborane nucleus. Success was achieved by ferric chloride-catalyzed elimination of an alkyl halide from equimolar mixtures of dichloroand dialkoxysilanes at temperatures of 140-165°C.…”
Section: Decaborane Skeletonmentioning
confidence: 99%
“…The earliest results using differential scanning calorimetry 16 showed that the polymers Dexsil 100, Dexsil 200, and Dexsil 300 were stable up to 500°C in an inert atmosphere. In air, however, only Dexsil 100 remained unchanged up to this temperature.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…The endothermic and exothermic deflections are in good agreement with previously reported differential scanning calorimetric measurements made at 500°C. 4 On the basis of the DTA thermogram obtained from a dimethylpolysiloxane the initial exothermic change exhibited by the copolymers in the temperature region of 250-450°C. can be reasonably associated with the oxidation of methyl groups.…”
Section: Differential Thermal Analysismentioning
confidence: 99%
“…Carboranes have been incorporated by various methods into polymers to improve oxidation resistance. In the 1960s, the first members of polysiloxanes with m-carborane units in the backbone of the polymers were prepared by the ferric chloride catalyzed elimination of an alkyl halide from equimolar mixtures of dichloro-and dialkoxysilanes (7). The polymers proved to be thermally stable to 500 C and oxidatively stable to about 350 C. In the 1970s, an alternating block copolymer containing m-carborane units was prepared by the reaction of a ureidosilane-terminated polysulfone hard block with a carboranesilanol-terminated carboranesiloxane oligomer (8).…”
Section: Introductionmentioning
confidence: 99%